Effect of methylene blue on the growth of bacteria isolated from patients with Atopic Dermatitis (Journal of the College of Basic Education, 2022)
The study aimed to determine the bacteriological profile and effect of antibiotic and methylene blue on bacteria isolated from atopic dermatitis patients . volume of samples were 100 patients from two hospitals in Baghdad province. After the swabs had been cultured on different media, conventional bio chemical tests to identify bacterial isolates and testing effect of antibiotic and methylene blue on growth of bacterial isolates. Out of the one hundred patients with eczema in all study groups , results showed that Staphylococcus aureus isolated at a highest percentage 20 (57.14%), followed by Staphylococcus haemolyticus 7 (20%), and Pseudomonas fluorescens 5 (14.28%) and two isolates of Enterobacter aerogenes (5.7%) ,and one isolate of Staphylococcus warneri(2.8%). All isolates lost ability to growth at concentration 10mg/ml of methylene blue, the MIC of the methylene blue against S. haemolyticus and P.fluorescens were (1) mg/ml, while against S .warneri and S.aureus were (10) mg/ml,Isolates showed high resistance to cloxacillin and Augmenten ,but more sensitive to Nitrofurantin